Bibliometric review of optimization and image processing of Positron Emission Tomography (PET) imaging system between 1981-2022 - Murat, Husain; Awang Kechik, Mohd Mustafa; Chew, Ming Tsuey; Kamal, Izdihar; Abdul Karim, Muhammad Khalis (Bentham Science, 2024)
Background: Positron Emission Tomography (PET) scan stands as a valuable diagnostic tool in nuclear medicine, enabling the observation of metabolic and physiological changes at a molecular level. However, PET scans have a number of drawbacks, such as poor spatial resolution, noisy images, scattered radiation, artifacts, and radiation exposure. These challenges demonstrate the need for optimization in image processing techniques. Objectives: Our objective is to identify the evolving trends and impacts of publication in this field, as well as the most productive and influential countries, institutions, authors, themes, and articles. Methods: A bibliometric study was conducted using a comprehensive query string such as “positron emission tomography” AND “image processing” AND optimization to retrieve 1,783 publications from 1981 to 2022 found in the Scopus database related to this field of study. Results: The findings revealed that the most influential country, institution, and authors are from the USA, and the most prevalent theme is TOF PET image reconstruction. Conclusion: The increasing trend in publication in the field of optimization of image processing in PET scans would address the challenges in PET scan by reducing radiation exposure, faster scanning speed, as well as enhancing lesion identification.